Rapid emergency response to yellow rust epidemics caused by newly introduced lineages of Puccinia striiformis f. sp. tritici in Argentina - Carmona, Marcelo Anibal; Sautua, Francisco José; Pérez-Hernández, Oscar; Grosso, Carlos; Vettorello, Lucas; Milanesio, Barbarina; Corvi, Eduardo; Almada, Gustavo; Hovmøller, Mogens Støvring (Springer, 2019)
Yellow rust (YR), caused by Puccinia striiformis f. sp. tritici, is one of the most destructive diseases of wheat worldwide. In 2017, YR emerged in Argentina and spread quickly into three million hectares, causing damage at levels only seen during the severe epidemics during the late 1930s. This widespread occurrence coincided with reports of newly introduced exotic races into the country. Therefore, little was known about actual impact of the disease on yield, reaction of commercial wheat cultivars, efficacy and best timing for fungicide applications. This study addressed these fundamental questions to provide a quick response to the re-emergence of YR in Argentina. Thirty wheat cultivars (short and long cycle) were evaluated for their response to a PstS13 lineage of Puccinia striiformis f.sp. tritici. The efficacy of one or two fungicide applications for controlling YR was also assessed. Disease severity reached about 50% in the untreated plots at early crop growth stages. Disease and yield data analyses showed that one fungicide application provided effective YR control, but two applications further secured a significant relative increase in yield. Grain yield was negatively correlated with disease severity, and losses reached up to 4,700 kg/ha in the untreated control plots for several varieties. We provide new and important information on the control of and potential yield losses by a new exotic race of Puccinia striiformis f.sp. tritici introduced to South America.